(3GdOYhi CeGe GdeMceI GdLfGFjI GdOhdjI (B:s (3OQGSI ebGQfI Hjf GdeMceI GdLfGFjI GdOhdjI hGdbGfhf GdhWfj (B/s - (3GdCMQej, YeQh jMji eMeOs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3JfGhdJ GdOQGSI ehVhY GdOYhi CeGe GdeMceI GdLfGFjI GdOhdjI OQGSI ebGQfI Hjf GdeMceI GdLfGFjI GdOhdjI hGdbGfhf GdhWfj, JeJ eYGdLJg aj EWGQ OQGSI ebGQfI Jdbj GdVhA Ydi eNJda LhGfHg, hMJi jMbb GdHGMK GdZGjI GdJj jgah EdjgG ef HMKg abO bSeg Edi ebOeI haUd JegjOj hHGHjf hNGJeI(B. (3aHjf aj GdebOeI CgejI GdehVhY hETcGdjJg hGdCgOGa GdeJhNGI efg hfWGbg hefGgL GdHMK GdeSJNOeI(B. (3ceG YQL ddOQGSGJ GdSGHbI GdJj cJHJ ajg(B. (3hJYQV aj GdaUd GdJegjOj dLPhQ fTCI GdeMceI GdLfGFjI GdOhdjI ef NdGd eMGceGJ GdMQH GdYGdejI GdChdi hGdKGfjI hGdeMGce GdLfGFjI GdOhdjI GdeDbJI aj GdMbHI GdJj SHbJ GdeMceI GdLfGFjI GdOhdjI(B. (3hNUU GdHGH GdChd dOQGSI GdeMceI GdLfGFjI GdOhdjI ef MjK WHjYJgG GdbGfhfjI hCfgG efXeI bGFeI Ydi eYGgOI OhdjI hCfgG OGFeI, hPGJ UaI YGdejI(B. (3hCf GdOYGhi GdJj JfXQ CeGegG JMcegG YOI eHGOF ef CgegG eHOC GdJcGed, hGdLSGeI, hYOe LhGR eMGceI GdTNU Yf GdaYd PGJg eQJjf, hCf jJe ESfGO GdGNJUGU Edi GdeMceI, hJMOjO GdbGfhf GdhGLH GdJWHjb(B. (3ceG CTGQ GdHGMK Edi GdLQGFe GdJj JNJU HgG hgj (B: (3LQjeI GdEHGOI GdLeGYjI, hGdLQGFe VO GdEfSGfjI, hLQGFe GdMQH, hLQGFe GdYOhGf(B. (3CeG GdHGH GdKGfj aEfg jfUH Ydi ELQGAGJ SjQ GdOYhi CeGe GdeMceI GdLfGFjI GdOhdjI ShGA ef MjK GdEMGdI hGdGOYGA Ce ef MjK ELQGAGJ GdeMGceI hEUOGQ GdCMcGe Ce ef MjK GdWYf aj gPg GdCMcGe(B.s
(3HHdjhLQGajI (B: (3UaMI (B425-450.s
Keywords: (3GdeMceI GdLfGFjI GdOhdjIs; (3GdOYhi GdLfGFjI (B((3bGfhf Ohdj(B)s; (3GdbGfhf GdOhdj GdLfGFjs; (3eMGceGJ GdMQHs; (3LQjeI GdEHGOI GdLeGYjIs; (3LQGFe VO GdEfSGfjIs; (3LQGFe GdMQHs; (3GdCOdI GdLfGFjIs